ESTUDO DA ATIVIDADE ANTIOXIDANTE DO Pleurotus ostreatus PARA BIODIESEL - PAVANELLO, GUILHERME POZZOBOM (2022)
Biodiesel is a renewable fuel, with several economic and environmental advantages. However, biodiesel may oxidize, then the need to use antioxidants. The antioxidants normally added indsutrially to biodiesel are synthetic ones, such as tert-butyl hydroquinone, TBHQ. In this study, mixtures of Pleurotus ostreatus (Shimeji mushroom), citric acid and vitamin E were analyzed as antioxidants for methylic soy biodiesel. Oxidative acceleration assays for biodiesel samples were performed using the Rancimat® equipment at 110 oC. Experimental design studies of the oxidative stability tests, for the use of Pleurotus ostreatus (P.O) in the concentration 5 g L-1, showed an induction period (P.I) of the order of 9.28 h; for the mixture P.O 2,5 g L-1 and 75 ppm of vitamin E, showed that the best PI found was 10.91 ± 0.09 h, indicating synergy in the kinetic antioxidant process of biodiesel, in addition to meeting the minimum PI required, according to EN 14214 Standard. This result indicated that the mixture P.O 2, 5 g L-1 and 75 ppm of vitamin E can be used to replace synthetic antioxidants for biodiesel. The kinetic tests showed that the oxidative process of biodiesel B100 (without antioxidant) follows the order 1 (k = 1.0277 s-1) and that in the presence of Pleurotus ostreatus in the mixture of 2.5 g L-1 and 75 ppm of vitamin E (k = 0.4758 s-1) followed the same order, resulting that in the presence of antioxidants there was no change in the kinetic process of biodiesel oxidation. The thermodynamic analysis of the misture P.O 2.5 g L-1 and 75 ppm of vitamin E, showed Ea=49.87 kJ mol-1, ΔH‡=46.61 kJmol-1, ΔS‡=-131.33 JK-1mol-1 and ΔG‡= 95.61 kJmol-1, being a non-spontaneous, endothermic oxidative inhibitory process and lower oxidative reactional disorganization, when compared to sample B100: Ea =29.06 kJ.mol-1, ΔH‡=25.80 kJmol-1, ΔS‡ =-179.20 JK-1 mol-1 and ΔG‡ = 92.67 kJ mol-1.